PENDAMPINGAN BELAJAR BERNUANSA ISLAMI MELALUI BIMBINGAN BELAJAR MATEMATIKA DI DESA RUWIT WEDUNG DEMAK - Putri Nur Malasari; Atikoh Atikoh; Umi Kamilia; Choirun Na'im (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2022)
On average, Elementary School and Madrasah Ibtidaiyah students in the village of Ruwit Wedung Demakhave difficulty completing homework assignments in mathematics. On the other hand, some parents have limited ability to teach mathematics at home. Based on this, this community service has the aim of developing motivation and achievement in learning mathematics by providing an Islamic learning experience in mathematics. The implementation of this service uses the service-learning method. This service activity involved 50 elementary and Madrasah Ibtidaiyah students. The learning mentoring process is carried out by dividing students into groups based on grade level. This service data analysis technique is descriptive narrative. The results of this service reveal that the motivation and achievement of learning mathematics in Ruwit village children are experiencing good development.